Management of the Hostile Abdomen - Lundy, Megan; Ashburn, Jean H. (Clinics in Colon and Rectal Surgery, 2022)
Caring for a patient with a hostile abdomen is one of the most challenging clinical situations one can encounter. It requires specialized technical skill coupled with bold but thoughtful decision-making to achieve good outcomes. An approach to the patient with a complex, hostile abdomen must be individualized to account for the patient's personal details. However, implementing an experienced-based algorithm to help make the difficult decisions required in this setting can be helpful, as evidence-based studies are few. The purpose of this review is to provide a structured, evidence, and experienced-based approach to the challenges that the surgeon encounters when faced with a patient with a hostile abdomen, and to discuss perioperative and intraoperative surgical strategies that can lead to most successful outcomes.
Keywords: hostile abdomen; revisional abdominal surgery; enteric fistula; dense adhesions